Mitochondrial replacement therapy: Genetic counselors' experiences, knowledge, and opinions. Issue 3 (19th January 2021) - Aryamvally, Anjali; Myers, Melanie F.; Huang, Taosheng; Slone, Jesse; Pilipenko, Valentina; Hartmann, Julianne E.
Abstract: Mitochondrial disorders affect at least 1 in 5, 000 individuals worldwide and are often incurable and fatal. Mitochondrial replacement therapy (MRT) is an in vitro fertilization technique used to prevent the transmission of mitochondrial disorders. Currently, MRT is the only approach that provides mothers who carry a pathogenic variant in their mitochondrial DNA (mtDNA), the opportunity to have a biological child without a mitochondrial disease. MRT involves the combination of nuclear DNA from the egg of the carrier mother and the cytoplasm from an oocyte donor, which contains healthy mitochondria. While MRT was approved for use in the UK in 2015, the ban on congressional funding for research on 'heritable genetic modification' has made MRT unavailable within the US borders. This survey‐based study aimed to describe genetic counselors' experience, knowledge, and opinions about MRT. Additionally, we also assessed whether genetic counselors' comfort discussing MRT with patients, and feelings about clinical use of MRT in the United States changed after providing information about MRT compared with baseline. Responses were received from 139 genetic counselors in North America. Findings indicate low awareness and knowledge about MRT among participants. However, more participants expressed comfort with discussing MRT with patients and more participants were able to form opinions about statements about MRT after they were provided with information about MRT. This study is the first to assess genetic counselors' opinions toward MRT and suggests the need for more education about novel technologies such as MRT among genetic counselors.